Pengendalian Pencemaran Limbah Domestik sebagai Upaya Rehabilitasi Pesisir di Desa Malangrapat, Kabupaten Bintan - Ginanjar Pratama; Itok Dwi Kurniawan; Aidil Fadli Ilhamdy (Universitas Sebelas Maret, 2020)
Title: Domestic Waste Pollution Control as Coastal Rehabilitation Efforts in Malangrapat Village, Bintan RegencyMalangrapat Village is one of the tourism destinations in the Bintan Regency area. The tourists who come every year makes the area experience a decrease in the quality of the environment due to domestic waste disposal. This can be seen from the amount of waste, and the reduction in fishing catches. The initial effort in preserving the coastal environment was the socialization of domestic waste control in the area. The role of the community to protect the tourism area in Malangrapat Village was very influential, considering that most of the people work as fishermen. The objective of this study was to educate the fishing community so that they know how to control the pollution of domestic waste. The stages of this study were the preparatory (coordination with the Head Village), a field study (a survey of domestic waste on the coast and survey of community knowledge about domestic waste), and the last was socialization-evaluation (the socialization about controlling domestic waste pollution and evaluation of water quality test). The results obtained from this study are increased public understanding of how to control domestic waste pollution in the area.